PENGARUH PENGEMBANGAN KARIR TERHADAP KEINGINAN BERPINDAH (TURNOVER INTENTION) (Studi Kasus Pada Karyawan PT. BFI Finance .Tbk Cabang Palembang) - Jauhari Hafiz; Badia Parizade; Agustina Hanafi (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2016)
This study to know the influence of career development toward turnover intention of employees. The independent variable in this study is the Career Development (X), and the dependent variable is Turnover Intention (Y). Data collection techniques in this study did not use sampling and use census. Distributing questionnaires to all of employees PT.BFI Finance, Tbk. Data analysis techniques used in this study is a simple linear regression and F test. Results indicate that career development has a negative and significant effect on employees turnover intentions, in others word the effect of variable (X) is inversely proportional to the career development variables (Y) turnover intention.Keywords : Career Delevopment, Turnover Intention, Employee